MODERN APPROACHES TO THE DIAGNOSIS AND SURGICAL TREATMENT OF CRANIOSYNOSTOSIS - Khakimov M.N., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Craniosynostosis is a craniofacial anomaly that requires timely diagnosis and surgical intervention to optimize neurological and aesthetic outcomes. Over recent decades, advances in imaging, surgical techniques, and perioperative care have significantly improved patient prognosis. This article discusses current diagnostic strategies, surgical treatment options, and long-term outcomes in children with craniosynostosis.